Recovering and deepening visions without blinders. Reflection inspired by the name of a magazine (Ágora de Heterodoxias, 2024)
This text is a reflection on scientific work and the publication of its results in academic journals, taking into consideration the environment relevant to human development in concrete situations.
Keywords: Academic research; knowledge; human development